Conductivity Studies of Silver‐, Potassium‐, and Magnesium‐Doped Hydroxyapatite. Issue 2 (26th August 2013) - Singh, Brajendra; Kumar, Samayendra; Basu, Bikramjit; Gupta, Rajeev
Abstract : We report the electrical transport properties of silver‐, potassium‐, and magnesium‐doped hydroxyapatites (HAs). While Ag+ or K + doping to HA enhances the conductivity, Mg +2 doping lowers the conductivity when compared with undoped HA. The mechanism behind the observed differences in ionic conductivity has been discussed using the analysis of high‐temperature frequency‐dependent conductivity data, Cole–Cole plots of impedance data as well as on the basis of the frequency dependence of the imaginary part (M″) of the complex electric modulus. The f max of modulus M″ decreased in silver‐ and potassium‐doped samples in comparison with the undoped HA.